Implementasi Metode Design Sprint Dalam Perancangan UI/UX Aplikasi Pembelajaran Interaktif - Dwiansyah, Zovanli; Rizaldinata, Wahyu; Mahesya, Abdan Fitra; Junadhi, Junadhi (STMIK Banjarbaru, 2023)
The continuously evolving world of education indirectly demands students to have a good understanding of various subjects in both school and higher education settings. Sometimes, the limited learning resources provided by educational institutions drive us to seek additional knowledge outside formal education. In the context of current educational innovation, technology has become an integral part of the learning process. The utilization of technology with new interaction patterns makes the roles of User Interface (UI) and User Experience (UX) increasingly crucial in meeting user needs. This research aims to discover ways to understand and fulfill user needs. Therefore, the author created a solution by designing an interactive UI/UX for a learning application. This research employed the design sprint method, involving five stages: understand, diverge, decide, prototype, and validate. The testing results using the System Usability Scale method yielded a score of